2015
DOI: 10.1002/pon.3838
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of self‐efficacy in the relationship between social support and post‐traumatic stress disorder symptoms among patients with central system tumors in China: a cross‐sectional study

Abstract: Self-efficacy partially mediated the relationship between social support and PTSD symptoms. Interventions focusing on both social support and self-efficacy might be more useful than interventions only targeting either of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The mediatorstested in our study differs from most previous studies [72, 7981], in which authors have mostly chosen self-efficacy [72], emotional abuse [79], sleep disturbances [80], and negative perception of social support [81]. Although Li [73] also suggested that resilience partially mediated the relation between psychological stress with depressive and anxiety symptoms, their research differed from ours in terms of population, dependent and independent variables, and even the resilience scale to some extent.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The mediatorstested in our study differs from most previous studies [72, 7981], in which authors have mostly chosen self-efficacy [72], emotional abuse [79], sleep disturbances [80], and negative perception of social support [81]. Although Li [73] also suggested that resilience partially mediated the relation between psychological stress with depressive and anxiety symptoms, their research differed from ours in terms of population, dependent and independent variables, and even the resilience scale to some extent.…”
Section: Discussionmentioning
confidence: 59%
“…Liu [64] demonstrated that PTSD symptoms are negatively associated with social support in patients with hematological malignancies in China. Wang [72] also confirmed that social support is negatively associated with PTSD symptoms in Chinese patients with central system tumors.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have revealed that positive psychological resources have considerable impact on chronic patients (e.g. cancer) and are remarkably important for one’s ability to recover from the current difficulties and to facilitate psychological well-being [32, 48, 54, 55]. In this study, social support, hope, resilience and self-efficacy were shown to be negatively correlated with depressive and anxiety symptoms in stroke survivors.…”
Section: Discussionmentioning
confidence: 60%
“…Although till now, studies in this field using a large sample size are scarce. Nonetheless, there were indications that these factors are strongly related to mood and quality of life of patients with other chronic conditions [16, 31, 32]. Therefore, we conducted the present study with following aims: Investigating the prevalence of psychological distress including depression and anxiety in stroke patients,Identifying the associations of psychological distress with positive psychological variables and ADL among stroke patients…”
Section: Introductionmentioning
confidence: 99%
“…The mediating role of self-efficacy in the relationship between social support and its positive health-related outcomes has been confirmed widely in patients with chronic diseases. 23 , 24 Moreover, self-efficacy can also act as a “moderator” to enhance or attenuate the effects of stressors and coping resources on psychological well-being. Yang et al 25 found that self-efficacy moderated the relationships of persuasion/pressure with diabetes-related emotional distress and depressive symptoms among older adults with type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%